THE EFFECTIVENESS OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) METHOD IN TEACHING READING SKILL VIEWED FROM STUDENTS’ INTEREST - Astuti, Desi Sri (Jurnal Pendidikan Bahasa, 2014)
This research aims at finding out whether: (1)Cooperative Integrated Reading And Composition (CIRC) Method is more effective than Direct Instruction Method to teach reading skill ; (2) the students who have high interest  have better reading skill  than those who have low interest; and (3) there is an interaction between teaching methods and students’ interest for teaching reading skill.This experimental study was conducted at SMAN 8 to the tenth grade students in the Academic Year of 2012/2013. Data analysis revealsresearch findingsas follows: (1) CIRC Method is significantly different from Direct Instruction Method to teach reading  skill; (2) The students who have high interest have better reading skill than those who have low interest; and (3) There is an interaction between teaching methods and students’ interest for teaching reading skill. Based on the findings, it can be concluded that in general CIRC Method is more effective than Direct Instruction Method to teach reading skill. For the students who have high interest, CIRC Method is more effective than Direct Instruction Method to teach reading skill but for the students who have low interest, Direct Instruction Method is more effective than CIRC Method to teach reading skill. The effectiveness of the method depends on the degree of the students’ interest. Keyword :CIRC Method, Direct Instruction, Reading Skill, Students’ Interest